Morphological and molecular characterization of species of Tulasnella (Homobasidiomycetes) associated with Neotropical plants of Laeliinae (Orchidaceae) occuring in Brazil - Almeida, Paulo Ricardo; van den Berg, Cassio; Goes-Neto, Aristoteles (Lankesteriana: International Journal on Orchidology, 2015)
Tullasnella spp. have been found forming mycorhizal associations with plants of all Orchidaceae subfamilies, and they are one of the main symbionts in partially micoheterotrophic plants (Taylor et al. 2002). Little is known about mycorhizal fungi of Neotropical Orchidaceae, especially in Laeliinae that occur in distinct environments such as “Restingas”, Seasonal Forests and “Campos Rupestres” (Cruz et al. 2003, Britto et al. 1993, França et al. 1997, Withner 2000).